Experimental Observation of Temperature and Pressure Induced Frequency Fluctuations in Silicon Mems Resonators - Zhao, Chun; Mustafazade, Arif; Pandit, Milind; Seshia A, Ashwin; Sobreviela, Guillermo; Zou, Xudong; Seshia, Ashwin A. (IEEE, 2021)
Silicon MEMS resonators are increasingly being adopted for applications in timing and frequency control, as well as precision sensing. It is well established that a key limitation to performance is associated with sensitivity to environmental variables such as temperature and pressure. As a result, technical approaches to address these factors such as vacuum sealing and ovenization of the resonators in a temperature controlled system have been introduced. However, residual sensitivity to such effects can still serve as a significant source of frequency fluctuations and drift in precision devices. This is experimentally demonstrated in this paper for a precision oven-controlled and vacuum-sealed silicon resonators. The frequency fluctuations of oscillators constructed using two separate nearly-identical co-located resonators on the same chip are analysed and differential frequency fluctuations are examined as a means of reducing the impact of common-mode effects such as temperature and pressure. For this configuration, our results show that the mismatch of temperature and pressure coefficients between the resonators ultimately limits the frequency stability.
Keywords: Semiconductor device measurement; Resonators; Silicon mems; Frequency measurement; Temperature sensors; Resonant frequency; Silicon; Noise processes; Temperature measurement; Pressure dependence; Temperature dependence